PENGARUH CURRENT RATIO (CR), BOOK VALUE (BV) DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA RETAIL TRADE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016 – 2019 - Bori Tiawarman; Riki (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to determine the influence of Current Ration (CR), Book Value (BV) and Net Profit Margin (NPM) on the Share Price of Retail Trade companies in IDX in 2016 – 2019. And to find out if there is a problem of the influence of Current Ratio (CR) on the Share Price of Retail Trade companies listed in IDX in 2016 – 2019, Is there any effect of Book Value (BV) on the Share Price of Retail Trade companies listed in IDX in 2016 – 2019, Is there any influence of Net Profit Margin (NPM) on the Share Price of Retail Trade companies listed in IDX in 2016 – 2019 and is there any influence of Current Ratio (CR) , Book Value (BV) and Net Profit Margin (NPM) against the Share Price of Retail Trade companies listed in IDX in 2016 – 2019. The methodology used is Multiple Linear Regression Analysis, Determination Kofisie, T Test and F Test. significant Current Ratio 0.437 > 0.05, Book Value 1.29 > 0.05 and Net Profit Margih 0.248 > 0.05 against a share price of 0.150 > 0.05.